Optimizing filler retention of mixed tropical hardwood based uncoated fine paper - Wahyudi, Ferdian Alam; Nazhad, Mousa M.; Basta, Jiri; Lehtinen, Esa; Asia Pacific Holding Ltd. (APRIL) Indonesia (Pathum Thani, Thailand : Asian Institute of Technology, 2011)
The objectives of this study was to evaluate the effects of different filler loading method, variation retention aid dosage and different structure of CPAM on furnish retention and drainage, with the aim of finding an effective process to improve filler share in fine paper without loss in strength. Mixed tropical hardwood pulp from Sumateran forest, blending PCC {u2013} GCC filler and broke from APRIL were used as the main furnish components of the handsheet. It was observed that pre - flocculation of fillers wisth c ationic starch or CPAM resulted in higher strength, but retarded drainage and slightly detiorated the formation. The retention was slightly low compare to conventional filler addition method. It was also observed that addition of two cationic polyelectrolytes for bringing the system zeta potential to the iso electric point is not required. In addition, a single cationic polyelectrolytes could indeed do the job. The effects of microparticles and Nanoparticles on retention system were also evaluated. Nanoparticles system had strong positive effects on drainage and retention, but detiorated formation, strength and optical properties. In contrast, microparticles system had ability develop better formation, strength and optical properties, but lower on drainage and retention. The morphological structure differences of CPAM were also examine. It was observed with that linear or dispersion polymer had no effect on polymer absorption potential. Long and linear CPAM polymer increase drainage as well as retention. The structured dispersion polymer, however, showed higher strength. In addition, the overall effects of CPAM either linear or structured on formation were negative
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Pulp and Paper Technology, School of Environment, Resources & Development
Thesis (M. Eng.) - Asian Institute of Technology, 2011
Keywords: Hardwoods -- Indonesia; Paper -- Quality